“Control biologico de alternativa brassicicola en brassica oleracea VAR. Capitata, con cepas nativas de Trichoderma spp en Lamas-Perú” - Paredes Tuesta, Franco Martín (2014)
In Aucaloma's Fundo of the San Martin National University - Tarapoto ,in the leve! experimental field in the year 2011 and beginning of 2012, it's presented the black spot of cabbage, which decreased the yield and quality , with the aim of obtain biological control, isolate and apply six native strains of the fungus Trichoderma spp, of the Bajo Mayo in the laboratory of Plant Health - Plant Pathology, located in the University City of Morales' district and experiment in Aucaloma's Fundo located 15 km of Morales' district, Latitude South 6 º 20 ', West Longitude 76 º 21', altitude 720 meters at:>ové.sea.levet area of tropical moist forest lite ( bh -PT) of San Antonio Cumbaza's district ,province and region of San Martin; under Block Design Complete Randomized with 8 treatments and 3 blocks, strain characteristics ( morphs ) of Trichoderma sp were evaluated, also the length, diameter and weight of cabbage heads at harvest and Economic Analysis will evaluate. We managed to isolate and multiply 6 strains of Trichoderma, CSH, CAH, CA1, CCU, CMA and CA3, CA3 with these heads were obtained with 23,2 cm length, circumference 44,533 cm, weight 652 g, weight of true leaves 403,33 g, yield 27 329,88 kg/ha. The lower incidence with CCU and CA 1 with 68 and 73, 33 %. The 6 strains of Trichoderma recorded lower leaf area affected between 7,19 % to 10,75 %. According to the Cost I Benefit and Benefit I Cost had the largest gain with T6 ( CA3 ) and T5 ( CMA ) Treatment. Keywords: Trichoderma, incidence, leaf area affected, native strains, biological control.